THE AWARENESS OF ISLAMIC INHERITANCE LAW IN MUHAMMADIYAH GROUPS AT MEDAN CITY - Isnina, Isnina; Wajdi, Farid (Journal of Community Research and Service, 2018)
AbstractThe purpose of this study is to describe people's understanding of the distribution of inheritance according to Islamic inheritance law. This research uses a descriptive method. The population of this study were Muhammadiyah residents in Medan City with a sample of 274 respondents, but the return and complete for data processing amounted to 234 samples.Based on the results of the study concluded that all levels of education elementary, junior high, high school, diploma and S1 or S2 no respondents who have low levels of legal awareness both male and female. However, most of Muhammadiyah of Medan City only know that the division of inheritance in Islamic law has been arranged, but the technique of dividing inheritance in Islam most of society do not master well. This is because they do not have a basic knowledge of how the division of Islamic inheritance law.The practice of dividing the inheritance of Muhammadiyah citizens of Medan City is very diverse, some are using the Islamic law, using customary law, using the method of family deliberation, by giving men and women equally. not a few finish to the Court made. Keywords: Legal Awareness, Division Of Inheritance,  Islamic Law